Two Different Models to Predict Ionic‐Liquid Diffraction Patterns: Fixed‐Charge versus Polarizable Potentials. Issue 1 (30th October 2014) - Campetella, Marco; Gontrani, Lorenzo; Leonelli, Francesca; Bencivenni, Luigi; Caminiti, Ruggero
Abstract This study reports the performance of classical molecular dynamics (MD) in predicting the X‐ray diffraction patterns of butylammonium nitrate (BAN) and two derivatives, 4‐hydroxybutan‐1‐ammonium nitrate (4‐HOBAN) and 4‐methoxybutan‐1‐ammonium nitrate (4‐MeOBAN). The structure functions and radial distribution functions obtained from energy‐dispersive X‐ray diffraction spectra, recorded newly for BAN and for the first time for 4‐MeOBAN and 4‐HOBAN, are compared with the corresponding quantities calculated from MD trajectories, to access information on the morphology of these liquids. The different behavior of two force fields, a polarizable multipole force field and a fixed‐charge one supplemented by an explicit three‐body term, is shown. The three‐body force field proves to be superior in reproducing the intermediate q range, for which the polarizable force field gives the wrong peak position and intensities. In addition, both models can correctly account for the presence or absence of a low q peak in the scattering patterns.